Global trends in research on aging associated with periodontitis from 2002 to 2023: a bibliometric analysis - Liu, Xiaomeng; Li, Hongjiao (Frontiers in Endocrinology, 2024)
Background: Aging has been implicated in many chronic inflammatory diseases, including periodontitis. Periodontitis is an inflammatory disease caused by long-term irritation of the periodontal tissues by the plaque biofilm on the surface of the teeth This work sought to visualize research hot spots and trends in aging associated with periodontitis from 2002 to 2023 through bibliometric approaches.Methods: Graphpad prism v8.0.2 was used to analyse and plot annual papers, national publication trends and national publication heat maps. In addition, CtieSpace (6.1.6R (64bit) Advanced Edition) and VOSviewer (version 1.6.18) were used to analyse these data and visualise the scientific knowledge graph. Results: The number of documents related to aging associated with periodontitis has steadily increased over 21 years. With six of the top ten institutions in terms of publications coming from the US, the US is a major driver of research in this area. journal of periodontology is the most published journal in the field. Journal of Periodontology and Journal of Clinical Periodontology are the most popular journals in the field with the largest literature. Periodontitis, Alzheimer's disease, and peri-implantitis are current hot topics and trends in the field. Inflammation, biomarkers, oxidative stress cytokines are current research hotspots in this field. Conclusion: Our research found that global publications regarding research on aging associated with periodontitis increased dramatically and were expected to continue increasing. Inflammation and aging, and the relationship between periodontitis and systemic diseases, are topics worthy of attention Severe periodontal OR TS=(Biological Aging)) OR TS=(Aging, Biological) AND (((TS=(periodontitis)) OR TS=(Periodontitides)) OR TS=(Pericementitis)) OR TS=(Pericementitides) ( Table 1 ) . Literature selection inclusion criteria for this study were as follows: (1) the full text of publications related to periodontitis and aging; (2) the articles and reviews manuscript category were in English; and (3) the article was published between January 1, 2002, and October 25, 2023. The criteria for exclusion were as follows (1) the topic was not related to periodontitis and aging, and (2) the article was a conference abstract, news, or briefing paper. We exported the plain text version of the paper. Graphpad prism